Separation of Variables and Contractions on Two-Dimensional Hyperboloid - Kalnins, E.; Pogosyan, G.S.; Yakhno, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
In this paper analytic contractions have been established in the R→∞ contraction limit for exactly solvable basis functions of the Helmholtz equation on the two-dimensional two-sheeted hyperboloid. As a consequence we present some new asymptotic formulae.